Analysis of sexist humour content in Lapor Pak! on Trans7 television - Al Aqilah, Laila Syahar Zainab; Maryani, Eni; Aristi, Nindi (ProTVF, 2025)
Background: Sexist humour in the mass media has a significant impact on gender perceptions in society, especially for women who are often victims of real actions. Purpose: This research aims to understand the meaning of humour that contains sexist elements towards women using message content analysis. Methods: This study uses a qualitative descriptive method with content analysis from Krippendorf. The data collection process is carried out through observation techniques, with an emphasis on the analysis of the content of the material or materials, such as text, images, audio or video. The use of this technique is expected to provide comprehensive and in-depth data on sexist humor in the comedy program "Lapor Pak!". Results: It was found that sexist humour words and behaviours, such as objectification, use of sexualised double meanings, celebrating sexist humour, and the selection of sexy guest stars in the segment, have a derogatory meaning towards women. These findings suggest that there is a pattern of verbal behaviour that can reinforce gender stereotypes and create an environment that is detrimental to women. The normalisation of insulting jokes can affect society's perception and attitude towards women in general. Therefore, increasing the use of humour in the context of mass media needs to be considered to create a more positive and inclusive representation. Conclusion: The verbal behaviour pattern of sexist humour in the show "Lapor Pak!" can reinforce gender stereotypes and create an environment that is detrimental to women. Implications: This comedy program carries sexist messages that degrade women several times, which are packaged with funny behaviour so that the audience readily accepts them; this strengthens the normalisation and sensitivity of sexual harassment.